Optimizing of preoperative computed tomography for diagnosis in patients with peritoneal carcinomatosis - Duhr, Carolin D.; Kenn, Werner; Kickuth, Ralph; Kerscher, Alexander G.; Germer, Christoph Thomas; Hahn, Dietbert; Pelz, Joerg O.W. (World Journal of Surgical Oncology, 2011)
Background and Objective: This study evaluates whether Computer Tomography is an effective procedure for preoperative staging of patients with Peritoneal Carcinomatosis.Method: A sample of 37 patients was analyzed with contrast enhanced abdominal Computer Tomography, followed by surgical staging. All Computer Tomography scans were evaluated 3 times by 2 radiologists with one radiologist reviewing 2 times. The efficacy of Computer Tomography was evaluated using the Spearman correlation coefficient. Correlations were analyzed by abdominopelvic region to assess results of the Peritoneal Carcinomatosis Index (PCI) aggregating the 13 regions. Surgical findings were compared to radiological findings.Results: Results indicate high correlations between the surgical and radiological Peritoneal Carcinomatosis Indices. Analyses of the intra-class correlation between the first and second reading of one radiologist suggest high intra-observer reliability. Correlations by abdominopelvic region show higher values in the upper and middle regions and relatively lower values in the lower regions and the small bowel (correlation coefficients range between 0.418 and 0.726, p < 0.010; sensitivities range between 50% and 96%; and specificities range between 62% and 100%).Conclusion: Computer Tomography represents an effective procedure in the preoperative staging of patients with PC. However, results by abdominopelvic region show lower correlation, therefore suggest lower efficacy. These results are supported by analyses of sensitivity and accuracy by lesion size. This suggests that Computer Tomography is an effective procedure for pre-operative staging but less for determining a tumor's accurate extent. © 2011 Duhr et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2025-12-15
Keywords: Carcinomatosis; Diagnosis; PCI